Application of Mendelian randomization: can we establish causal risk factors for type 2 diabetes in low-to-middle income countries? - Langdon, Ryan James Quentin; Wade, Kaitlin Hazel (Revista Cuidarte, 2017)
The global burden of type 2 diabetes (T2D) is increasing, partially facilitated by a sharp increase in the disease in low and middle income countries (LMICs). LMICs not only show a high prevalence of T2D (8.7%), but have shown a much faster increase in this prevalence over the past 30 years when compared to high-income countries (HICs). Conventional risk factors for T2D in HICs, such as high body mass index (BMI), low levels of physical activity, and poor dietary behaviours, do not fully account for the greater increase in prevalence of T2D in LMICs. Therefore, risk factors for T2D specifically within an LMIC context need to be determined. How to cite this article: Langdon RJQ, Wade KH. Application of Mendelian randomization: can we establish causal risk factors for type 2 diabetes in low-to-middle income countries? Rev Cuid. 2017; 8(1): 1391-406. http://dx.doi.org/10.15649/cuidarte.v8i1.373